Agronomic performance of niger according to period of sowing in the south region of Mato Grosso do Sul - Bottega, Simone Priscila (2013)
Niger (Guizotia abyssinica) is a dicotyledonous annual herbaceous plant, which belongs to the family Asteraceae. Its seed is important to oil production in Ethiopia and in parts of India. Niger seeds have 30-40% oil, which is used to feeding and production of paints and soaps. In Brazil, its use is mainly restricted to feeding birds. It is considered that the ideal time for seeding is within a period that provides favorable climate for the culture and unfavorable to the incidence of diseases and pests. Thus, the objective of this study was to evaluate the agronomic performance of the culture of niger under different sowing periods. The research was conducted in the Experimental Farm of FCA-UFGD, located in Dourados-MS, during the agricultural year of 2011. The experimental design adopted was randomized blocks, with seven sowing periods, fourteen days spaced from each other, on 26/01, 09/02, 23/02, 09/03, 23/03, 06/04 and 20/04 in 2011, with four repetitions. Sowing in January and February increased the duration of the growing season and crop’s cycle. Seeding on April 6 resulted in higher productivity of niger seeds. The content of nitrogen, protein and oil were not affected by sowing periods.